Do partly outdated palaeontological data produce just a noise? An assessment of the Middle Devonian-Mississippian biodiversity dynamics in central Asia on the basis of Soviet-time compilations - Ruban, Dmitry (Geologos, 2011)
Interregional tracing of trends and events in the biotic evolution is an important task of modern palaeobiology. In Soviet times (1917-1991), numerous palaeontological data have collected for the territory of Russia and neighbouring U. S. S. R. countries. Later, these data were compiled and published in a series of reference volumes. Although this information cannot be updated in a conventional way, it remains valuable for quantitative analyses, particularly because of its comprehensive and unique character. Assessment of the previously collected data on the stratigraphic distribution of Middle Devonian-Mississippian marine invertebrates in three regions of central Asia (central Kazakhstan, Uzbekistan and Tajikistan) reveals some general patterns of biodiversity dynamics. The total number of genera generally declined during the Givetian-Famennian, whereas a remarkable diversity peak occurred in the Visean. This is consistent with the global pattern and, thus, permits to hypothesize a regional signature of the global trends. Changes in the extinction rate differ, however, between central Asia and the Earth in its entirety, which may be explained particularly by biases in either the regional or the global records. Evidence of the Givetian and Frasnian/Famennian mass extinctions is found in the three regions under study. Results of this tentative study indicate important directions for further research and suggest that central Asia is a highly important domain for studies of mid-Palaeozoic biodiversity dynamics.